2017
DOI: 10.1111/1754-9485.12675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interruptions of external beam radiation therapy on outcomes in patients with prostate cancer

Abstract: Unintentional treatment breaks during dose escalated external beam radiation therapy for PCa did not cause a significant difference in outcomes, although duration of follow up limits the strength of this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…Dong et al [15] reported outcomes on PCa patients treated with a dose ≥ 74 Gy, excluding those on ADT, and found no differences with outcomes in disease risk group using a 4 fraction threshold to define a lengthy treatment break. D’ambrosio et al [16] identified an increased non-treatment day ratio (NTDR, number of non-treatment days divided by the total elapsed days of RT) as an adverse factor in PCa patients treated with a median dose of 76 Gy, specifically in low-risk patients, but not intermediate, high, or all groups combined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dong et al [15] reported outcomes on PCa patients treated with a dose ≥ 74 Gy, excluding those on ADT, and found no differences with outcomes in disease risk group using a 4 fraction threshold to define a lengthy treatment break. D’ambrosio et al [16] identified an increased non-treatment day ratio (NTDR, number of non-treatment days divided by the total elapsed days of RT) as an adverse factor in PCa patients treated with a median dose of 76 Gy, specifically in low-risk patients, but not intermediate, high, or all groups combined.…”
Section: Discussionmentioning
confidence: 99%
“…Although the analyses by Amdur predated the PSA era, they included patients who would currently be staged as T3b. The remaining analyses [12,13,15,17] found no difference in patients with or without TI. In addition, all previous studies used EBRT treatments with photons.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…L'impact de l'étalement sur le contrôle du cancer de prostate est très discuté [28]. Certaines études récentes, basées sur des patients traités avec des doses supérieures ou égales à 70 Gy, ne retrouvent aucun effet de la durée totale de traitement sur tous les paramètres considérés (contrôle local, survie sans métastases, survie spécifique, survie globale) [29]. A contrario, dans une étude plus ancienne, Thames et al ont retrouvé un effet délétère de l'étalement, et en particulier, paradoxalement, chez les patients à faible risque [30].…”
Section: Cancer De La Prostateunclassified
“…For instance, a 1991 pooled analysis of Radiation Therapy Oncology Group trials 75-06 and 77-06 found no correlation between treatment time and local control or overall survival in a heterogenous patient population treated to 65 Gy, and similar findings were reported in a more recent study for patients treated to at least 74 Gy. 3,4 Conversely, Amdur et al noted that prolonged treatment times over 8 weeks for prostate cancer treated to 65-70 Gy had inferior local control, as did another analysis by Liauw and colleagues (although no difference was noted above 74 Gy). 5,6 Notably, most of these studies were not conducted with patients treated with dose-escalated radiotherapy and ADT.…”
Section: Introductionmentioning
confidence: 95%